Effect of simulated acidification on soil properties and plant nutrient uptake of eggplant in greenhouse - Wang, Tianqi; Yu, Leixin; Wang, Zhen; Yang, Chuang; Dong, Feiyu; Yang, Diwen; Xi, Haijun; Sun, Zhouping; Bol, Roland; Awais, Muhammad; Yang, Lijuan; Fu, Hongdan (Frontiers in Plant Science, 2025)
Soil acidification adversely affects plant growth and development by decreasing the accessibility of roots to essential nutrients. Thus, it decreases crop yield. However, there has been a lack of systematic research on how soil acidification influences nutrient absorption in eggplant cultivated in greenhouse. To address this research gap, an experiment was conducted in a greenhouse with seven different acidity levels (4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5), achieved by adding dilute H2SO4. The findings indicated that the soil organic matter (SOM) content at pH 4.5 decreased by 49% - 50% compared to pH levels of 7.0 - 7.5. In addition, the levels of exchangeable aluminum (Al3+) and soil electrical conductivity (EC) were highest at pH 4.5, with increases of 82 -88 mg kg-1 and 1.78 - 1.82 ms cm-1, respectively, compared to pH 7.0 - 7.5. The total nitrogen (TN), phosphorus (TP), and potassium (TK) content in the soil declined as acidity increased, reaching their lowest levels of 0.59, 0.42, and 3.79 g kg-1 at pH 4.5. Among the available nutrients, only potassium levels did not exhibit significant variation across treatments. However, the levels of macro elements in the soil consistently decreased, while the concentrations of trace elements (Fe, Cu, Zn) increased with rising acidity; conversely, the levels of other trace elements (B, Mo, Mn) decreased. The amounts of exchangeable calcium (Ca2+) and magnesium (Mg2+) at pH levels of 4.5 - 5.0 dropped by 61% - 66% and 70% - 78%, respectively, compared to pH 7.5. Further analyses indicated that soil pH values between 6.0 - 4.5 reduced the nutrient absorption capacity of eggplant, with the lowest nutrient content observed at pH 4.5. Mantel analyses confirmed that soil pH significantly affects plant nutrient uptake. This research provides both theoretical insights and practical guidance for the effective management of vegetable soil in greenhouse.